2014
DOI: 10.1177/0956462414562477
|View full text |Cite
|
Sign up to set email alerts
|

High rates of baseline antiretroviral resistance among HIV-infected pregnant women in an HIV referral centre in Rio de Janeiro, Brazil

Abstract: In order to understand antiretroviral resistance during pregnancy and its impact on HIV vertical transmission, we performed a cross-sectional analysis of 231 HIV-infected pregnant women who fulfilled Brazilian guidelines for antiretroviral testing and had antiretroviral genotypic testing performed between April 2010 and October 2012. At entry into prenatal care, the mean CD4 cell count for this cohort of patients was 406 cells/mm(3) (95% CI: 373-438 cells/mm(3)), while the mean HIV RNA was 24,394 copies/ml (95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
4
10
0
Order By: Relevance
“…Our study's results reveal that DRMs can commonly affect HIVinfected individuals despite the lack of prior ARV exposure, with DRMs affecting >10% of treatment-naive pregnant women and their infants. In Brazil, a 10.4% rate of DRMs in pregnancy found in this study agrees with most other studies evaluating ARV drug resistance in pregnant women, with rates ranging from 9% to 13% [15][16][17]. More recent reports are showing a trend toward higher rates of DRMs in pregnant women in Rio de Janeiro, with a prevalence rate of 17.2% in treatment-naive patients [18].…”
Section: Discussionsupporting
confidence: 90%
“…Our study's results reveal that DRMs can commonly affect HIVinfected individuals despite the lack of prior ARV exposure, with DRMs affecting >10% of treatment-naive pregnant women and their infants. In Brazil, a 10.4% rate of DRMs in pregnancy found in this study agrees with most other studies evaluating ARV drug resistance in pregnant women, with rates ranging from 9% to 13% [15][16][17]. More recent reports are showing a trend toward higher rates of DRMs in pregnant women in Rio de Janeiro, with a prevalence rate of 17.2% in treatment-naive patients [18].…”
Section: Discussionsupporting
confidence: 90%
“…An exception is a small study in 24 pregnant women performed in 2009–2010 in Rio de Janeiro that showed no evidence of TDR [ 76 ]. Of note, the most recent survey in 231 pregnant women performed in 2010–2012 in Rio de Janeiro showed high-level TDR to any ARV drug [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…The low prevalence of HIV-1 strains that are resistant to this class of drugs reflects the low circulation of viruses with resistance to PIs in the North region of the country [25], differently from what was observed in Rio de Janeiro [26] and in Goias [27] with a prevalence level around 16%.…”
Section: Discussionmentioning
confidence: 99%